Subchronic oral administration of crude khat extract (Catha edulis forsk) induces schizophernic-like symptoms in mice. Issue 1 (December 2016) - Bogale, Tegegne; Engidawork, Epherm; Yisma, Engida
Abstract Background Chewing fresh leaves of the khat plant (Catha edulis forsk) is a deep rooted and widespread habit in East Africa and the Middle East. Although a body of knowledge exists about the adverse effects of khat on health, data are sparse with regard to the consequences of long-term khat chewing in resulting schizophrenic like symptoms. Methods A crude extract of khat at different doses (100 mg/kg (K (khat)100), 200 mg/kg (K200) and 400 mg/kg (K400)) were administered for experimental group of mice whereas standard (ketamine (KT) 10 mg/kg- positive controls (KT10)) and vehicle (2 % v/v Tween-80 in distilled water – negative control groups (CON)) were administered for control groups of mice daily for two months to evaluate subchronic oral administration of crude khat extract to induce schizophrenic-like symptoms in mice. Mice were subjected to a battery of behavioural tests and parameters like locomotor activity, total time spent in social interaction and level of cognition among different groups of mice were measured and analyzed. Results Khat at all doses significantly increased (p  < 0.001) the mean locomotor activity score of mice compared to CON. However, the mean locomotor activity score of mice treated with khat was significantly lower (p  < 0.001) compared to the mean locomotor activity score of KT10 mice (p  < 0.001). The mean total time score (in seconds) spent in social interaction, mean total time score (in seconds) spent in sniffing and following the partner was significantly higher (p  < 0.001) in CON groups of mice compared to khat and ketamine treated groups. Moreover, in spatial memory task, the mean latency score (in seconds) to find the platform of khat and ketamine treated mice was significantly higher (p  < 0.05) when compared to CON. Conclusions Subchronic oral administration of khat showed an enhanced locomotor activity, reduced social interaction and impaired cognitive function, which demonstrated that long-term use of khat is associated with schizophernic-like symptoms.